Long-run improvements in human health: Steady but unequal - Ana Lucia Abeliansky; Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
There exists a steady trend at which later born cohorts, at the same age, are healthier than earlier born cohorts. We show this trend by computing a health deficit index for a panel of 14 European Countries and six waves of the Survey of Health, Aging, and Retirement in Europe (SHARE). We find that for each year of later birth, health deficits decline by on average 1.4 - 1.5 percent with insignificant differences between men and women, between countries, and over time. We argue that this trend approximates the rate of medical progress, broadly defined. The steady progress implies substantial delays of human aging. For example, the level of health deficits experienced at age 65 by individuals born 1920 is predicted to be experienced at age 85 by individuals born 1945. The potential health gains are not fully appropriated by individuals of low socio-economic status. Their health deficits decline at about the same rate but from a higher level, which means that we find long-run persistence of health inequality.
Keywords: I10; I14; I15; I24; 330; health; aging; health deficit index; medical progress; health inequality